2018
DOI: 10.1002/ajmg.b.32682
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric genetics researchers' views on offering return of results to individual participants

Abstract: In the middle of growing consensus that genomics researchers should offer to return clinically valid, medically relevant, and medically actionable findings identified in the course of research, psychiatric genetics researchers face new challenges. As they uncover the genetic architecture of psychiatric disorders through genome-wide association studies and integrate whole genome and whole exome sequencing to their research, there is a pressing need for examining these researchers' views regarding the return of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…In addition, there are aspects of psychiatric genetics research that make scalable and responsible return of results particularly challenging. 10 The large samples necessary to detect small effect sizes of genomic loci that contribute to the overall risk for these disorders raise the cost of returning individual results in these studies. 1,3 Further, the polygenic nature of psychiatric disorders and the important role of environmental factors in psychiatry may complicate the interpretation of research findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are aspects of psychiatric genetics research that make scalable and responsible return of results particularly challenging. 10 The large samples necessary to detect small effect sizes of genomic loci that contribute to the overall risk for these disorders raise the cost of returning individual results in these studies. 1,3 Further, the polygenic nature of psychiatric disorders and the important role of environmental factors in psychiatry may complicate the interpretation of research findings.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing consensus that some clinically relevant findings should be offered to individual participants in genomics research, 6,8,[16][17][18] including psychiatric genetics, 10,[19][20][21] there is little empirical data about how to ideally manage return of results (RoR) in the psychiatric genetics research context. 22,23 Most research on RoR in genetics research has focused on whether results should be offered, and the perceived risks and benefits of returning results, [7][8][9]18,24,25 along with which types of results (e.g., medically actionable, clinically valid but not actionable) are justifiable and recommended to return.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, studies indicate that patients with mental health disorders, their relatives, and clinicians overwhelmingly favor offering return of results for individual participants (Sundby et al, ). In a study published in this issue, Kostick, Brannan, Pereira, and Lázaro‐Muñoz () reported that the vast majority of psychiatric genetics researchers interviewed also support the return of at least some findings. However, return of results does not seem to be a common practice in psychiatric genetics research; 22% of researchers reported that they are offering return of results in at least one study (Kostick et al, ).…”
Section: Psychiatric Genetics In Research Settingsmentioning
confidence: 99%
“…Kostick and colleagues () present results from 39 interviews with psychiatric genetics researchers from around the world on the topic of return of results to individual participants in psychiatric genetic research. Researchers overwhelmingly favored offering some findings to individual participants, but expressed concerns regarding how this information may affect patient‐participants, logistics and resources for returning results, and how the information should be offered and returned in a responsible way.…”
mentioning
confidence: 99%